2011
DOI: 10.1371/journal.pone.0028661
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Trace-Level DNA by Real-Time Whole Genome Amplification

Abstract: Quantification of trace amounts of DNA is a challenge in analytical applications where the concentration of a target DNA is very low or only limited amounts of samples are available for analysis. PCR-based methods including real-time PCR are highly sensitive and widely used for quantification of low-level DNA samples. However, ordinary PCR methods require at least one copy of a specific gene sequence for amplification and may not work for a sub-genomic amount of DNA. We suggest a real-time whole genome amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The DNA–RNA chimeric product was exponentially produced with as little as 300 nM enzyme and 0.2 nM template, except with the 12 + 12 template, which required 2 nM template (Figure B and Figures S4–S7). As observed in other studies, slight decreases in fluorescence were observed in the qPCT curves at long times, which is likely due to SYBR green I dye instability. Product was confirmed by PAGE (Figure C and Figures S4–S7), and the desired RNA oligonucleotide was easily obtained by incubation with TurboDNase (Figures F and S9).…”
Section: Resultssupporting
confidence: 82%
“…The DNA–RNA chimeric product was exponentially produced with as little as 300 nM enzyme and 0.2 nM template, except with the 12 + 12 template, which required 2 nM template (Figure B and Figures S4–S7). As observed in other studies, slight decreases in fluorescence were observed in the qPCT curves at long times, which is likely due to SYBR green I dye instability. Product was confirmed by PAGE (Figure C and Figures S4–S7), and the desired RNA oligonucleotide was easily obtained by incubation with TurboDNase (Figures F and S9).…”
Section: Resultssupporting
confidence: 82%
“…The contamination level of the host cell nucleic acid content in the purified mAb was determined by qPCR analysis. The assay was based on a previous work (Kang et al 2011 ). Briefly, a standard curve from 5 nanogram to 500 attogram of DNA was generated from a CHO-K1 cell DNA stock (IDT, Coralville, Iowa, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The primers of DOP-PCR are placed at the 3' end, randomly in the middle, and at the 5' end. This method has been successfully demonstrated in the determination of the human placental DNA ranging from 80fg to 8ng [43].…”
Section: Polymerase Chain Reaction (Pcr) Amplificationmentioning
confidence: 99%